2009
DOI: 10.1111/j.1744-313x.2009.00841.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA genes in Uros from Titikaka Lake, Peru: origin and relationship with other Amerindians and worldwide populations

Abstract: Uros population from the Titikaka Lake live in about 42 floating reed ('totora') islands in front of Puno City (Peru) at a 4000 m high altiplano. They present both an mtDNA and a human leucocyte antigen (HLA) profile different from the surrounding populations: mtDNA A2 haplogroup is common to Uros and Amazon forest lowland Amerindians. HLA genetic distances between populations have been calculated and neighbour-joining dendrograms and correspondence analyses were carried out. Approximately 15 006 HLA chromosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 37 publications
1
15
0
1
Order By: Relevance
“…The genetic relatedness among Amerindians, Na-Dene, Eskimos, Asians, Negroids, Europeans and Polynesians are determined by calculating the genetic distances between populations (DA), using HLA-DRB1 allele frequencies. Amerindians cluster together and separated from the rest of the World populations [14,34,35,37]. …”
Section: Fig (1)mentioning
confidence: 99%
See 2 more Smart Citations
“…The genetic relatedness among Amerindians, Na-Dene, Eskimos, Asians, Negroids, Europeans and Polynesians are determined by calculating the genetic distances between populations (DA), using HLA-DRB1 allele frequencies. Amerindians cluster together and separated from the rest of the World populations [14,34,35,37]. …”
Section: Fig (1)mentioning
confidence: 99%
“…These relationships are calculated in n dimensions and represented in two dimensions. Circles represent an approximate grouping of populations [14,34,35,37]. …”
Section: Fig (1)mentioning
confidence: 99%
See 1 more Smart Citation
“…Principal Components Analysis (PCA) for 38 populations with HLA-B data available was performed using the IBM SPSS Statistics 19 software ( IBM Corporation, Armonk, NY, USA ) to analyse the distribution of HLA-B alleles in human groups of the proposed ancestries, Figure 1 . PCA included population data of Ireland [20], NW of England [61], Germany [62], Austria [63]; Spain, Italy, United Kingdom [64], France [65], Gypsy from Andalucía (Spain; data collected by López-Nevot et al ) [14], Azores Terceira Island [66], Forro from São Tomé Island [67], Beti from Cameroon [68], Bandiagara from Mali, Lusaka from Zambia, Luo and Nandi from Kenia [69], Mandeka from Senegal [70], Guinea Bissau [71], Aleut from Bering Island (Russia) [72], center of Japan [73], a cord blood bank of Tzu Chi Foundation (Taiwan) [74], Han from southern China [60], north India [75], Kensiu from Malasya [76], Kinh from Vietnam [77], Tarahumara from northern Mexico [17], Native Americans from Gila River (USA) [78], Yu’pik from Alaska (USA) [79], Mixtec, Zapotec, and Mixe from Oaxaca (Mexico) [16], Seri from Sonora (Mexico) [80], Navajo from New Mexico (USA) [81], Uro from Titikaka Lake (Peru) [82], and Toba from Rosario (Argentina; data collected by Cintia Marcos et al ) [14]. Also, two admixed populations from Mexico were included: a “Mexican Mestizo” sample [83] and a sample from Guadalajara City, western Mexico [23].…”
Section: Methodsmentioning
confidence: 99%
“…However, few genetic studies have been conducted with Uros communities. A previous study of HLA profiles [16] suggested an ancient connection between the Uros from Puno and Amazonian ethnic groups, following an old hypothesis of connection between Uruquilla (original language of the Uros) and the Arawak linguistic branch [7], [8]. Other genetic studies using mtDNA [17], [18] suggested that the Uros from Lake Titicaca still conserve part of their own ancient genetic background, while also forming a heterogeneous group.…”
Section: Introductionmentioning
confidence: 96%